THE CONCEPT OF ‘SUCCESSFUL COLLEGE STUDENT’ IN YOGYAKARTA PROTOTYPE SEMANTICS - Muhammad Hafiz Kurniawan; Ulaya Ahdiani (Universitas Putera Batam, 2020)
Manipulation and even murder case done by student to the teacher shocked Indonesians. These unexpected phenomena happened in university – the place where the students achieve their dreams and the new knowledge to nourish their brains – because of the undergraduate thesis. Therefore, this research aimed to discover the concept of “successful college student” in the respondents’ mind. The respondents were 200 students majority from one of private universities and twodifferent universities in Yogyakarta for each method. This concept portrayed the ideal college student in their mind by revealing the most ideal and successful student, so the goal of the college students can be well-described. This research used free listing with limited time, 30 seconds as the first step of collecting the data and judging the illustration as the second one. The first method was used to create the criteria that should be included in the illustrations. Those illustrations were judged by the respondents using semantic scale, 1-7 to represent from failed to successful. The result of this research showed the gradation of member in the concept of “successful college student” was different in age, semester and discipline category but they shared common prototypical concept that the successful college student should have high GPA, be smart, diligent and religious, and should graduate on time.